The Conversational Implicature Analysis on Into the Magic Shop Novel by Dr. James R. Doty - Ni Luh Putu Aprilia Ammara Harleyda Dewi; Ni Made Diana Erfiani; Gek Wulan Novi Utami (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2022)
AbstrakImplikatur percakapan tidak hanya ditemukan dalam percakapan lisan, tetapi juga dapat ditemukan dalam percakapan tertulis seperti dalam karya sastra seperti novel. Seperti dalam novel karya Dr. James R. Doty yang berjudul Into the Magic Shop: A Neurosurgeon's Quest to Discover the Mysteries of the Brain and the Secrets of the Heart, pengarang banyak menyisipkan percakapan yang mengandung implikatur percakapan yang dapat dikenali melalui konteksnya. diceritakan dalam cerita. Penelitian ini bertujuan untuk menemukan jenis implikatur percakapan yang digunakan oleh tokoh novel Into the Magic Shop karya Dr. James Robert Doty yang diterbitkan pada tahun 2016 oleh Avery New York. Pengumpulan data dilakukan dengan metode note--taking. Penelitian dilakukan dengan menggunakan pendekatan deskriptif-kualitatif. Pendekatan deskriptif-kualitatif digunakan untuk menampilkan fenomena kebahasaan yang terdapat dalam novel dan mengamati ekspresi ujaran yang disampaikan dalam novel Into the Magic Shopyang diinterpretasikan dengan menggunakan deskripsi. Hasil penelitian menunjukkan, dari 27 implikatur percakapan yang ditemukan, 5 ujaran dikategorikan ke dalam implikatur percakapan umum, 14 ujaran menjadi implikatur berskala, dan 8 ucapan termasuk dalam implikatur percakapan khusus. Jenis implikatur yang dominan ditemukan adalah implikatur berskala karena novel ini adalah kisah hidup penulis (Dr. Doty) yang mempelajari keterampilan dan sebagian besar menggunakan skala untuk mengekspresikan topik tuturan.Kata kunci: Implikatur percakapan, Pragmatik, Novel, Into the Magic Shop, Ke Dalam Toko SulapAbstractConversational implicature not only found in oral conversation, but it also can be found in writen conversation such as in literary works like novel. As in the novel by Dr. James R. Doty entitled Into the Magic Shop: A Neurosurgeon's Quest to Discover the Mysteries of the Brain and the Secrets of the Heart, the author inserts many conversations that contain conversational implicatures that can be recognized through the context narrated in the story. This study aims to find the type of conversational implicature used by the novel’s character. The data was taken from Into the Magic Shop novel by Dr. James Robert Doty that published on 2016 by Avery New York. There are conversations found that contains conversational implicature. The data collected using the note-taking method. The study was conducted using descriptive-qualitative approach. A descriptive-qualitative approach used because it describes the linguistic phenomena found in the novel and observed the utterance expression conveyed in the Into the Magic Shop novel that interpreted using description. The result shows, from 27 conversational implicature found, 5 utterances categorized into generalized conversational implicature, 14 utterances into scalar implicature, and 8 utterances into particularized conversational implicature. The dominant type is scalar implicature as this novel is a life story of the author (Dr. Doty) who learn a skill and mostly used scale to express the topic of the utterances.Keywords: Conversational Implicature, Pragmatics, Novel, Into the Magic Shop